The role of customer engagement in enhancing repurchase intention and eWOM through technology-driven experiences: A stimulus-organism-response perspective of Xiaohongshu - Xiaodan, Chen; Suwandej, Niyom (Edelweiss Applied Science and Technology, 2025)
This study investigates the role of customer engagement in enhancing repurchase intention and electronic word-of-mouth (eWOM) through technology-driven experiences on Xiaohongshu, using the Stimulus–Organism–Response (S-O-R) model. Drawing on a mixed-methods approach, the study examines how social interaction, information quality, and perceived value (stimuli) influence cognitive, emotional, and behavioral engagement (organism), which in turn affect repurchase intention and eWOM (responses). Quantitative data from 407 Xiaohongshu users in Shanghai and qualitative insights from 17 in-depth interviews reveal that all hypothesized relationships are supported. The findings highlight that platform-driven stimuli significantly shape user engagement and that engagement is a key driver of loyalty and advocacy. The integration of technology, content quality, and user community experience creates a robust foundation for sustained behavioral outcomes. This research contributes to the literature on digital engagement and offers practical insights for optimizing social commerce strategies.